Delirium and Anxiety Outcomes Related to Visiting Policy Changes in the Intensive Care Unit During the COVID-19 Pandemic - Kim, Bomi; Cho, Jaehwa; Park, Jin Young; Kim, Hesun Erin; Oh, Jooyoung (Frontiers in Aging Neuroscience, 2022)
Objective To evaluate the effect of intensive care unit (ICU) visit on the incidence of delirium, delirium subtype, and anxiety level in ICU patients. Methods Trained psychiatrists and nurses evaluated ICU patients for delirium, delirium subtypes, and anxiety. Propensity score matching (PSM) was used to retrospectively analyze the data. Then, we compared the differences in the incidence of delirium, delirium subtypes, and anxiety level before and after the ICU visit ban. Logistic regression was conducted to identify the risk factors for delirium subtypes and high anxiety levels. Results After PSM, there was no statistically significant difference in the incidence of delirium between the non-visiting and restrictive visiting groups (p=.162). The proportion of hyperactive and mixed subtypes was higher in the non-visiting than in the restrictive visiting group (p=.002). The anxiety level was higher in the non-visiting than in the restrictive visiting group (p=.009). Patients who stayed in the ICU during the visit ban were more likely to have hyperactive (p=.005) and mixed subtype (p=.001) than those who did not. Moreover, patients who stayed in the ICU during the visit ban were more likely to experience high anxiety levels than those who did not (p<.001). Conclusion Prohibition of ICU visits did not affect the incidence of delirium during COVID-19 but could change the delirium subtype and raise anxiety level. Moreover, visiting prohibition was a risk factor for non-hypoactive delirium subtype and high anxiety levels. Therefore, ICU visits are important in dealing with delirium subtypes and anxiety in ICU patients.